Advances in Design, Music and Arts : 7th Meeting of Research in Music, Arts and Design, EIMAD 2020, May 14-15, 2020 /: 7th Meeting of Research in Music, Arts and Design, EIMAD 2020, May 14-15, 2020. ([2021]) - Unknown
No abstract available